(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
Certain suppliers choose to distribute their products through commercial agents. Due to special features of this particular commercial relationship, for the purpose of EU competition law the agent is considered to form an integral part of supplier’s undertaking and as a consequence, the agreement between the two falls out of the scope of competition rules. The aim of this article is to demonstrate the importance of the EU competition law criteria for agency qualification and the existent ambiguities in that regard, with a view of providing a much-needed clarification in the context of online platforms. To this end, the authors first provide a brief overview of CJEU and EU Commission development related to agency agreements, followed by a comparative NCA’s analysis of the market-specific investments as the most critical agency criteria when it comes to online platforms business models. Finally, authors analyze the revisions of Vertical Guidelines proposed during the EU Commission’s evaluation of VBER. The authors argue that Vertical Guidelines should make a clear distinction between online platform’s investments that are specifically related to the relevant market and investments which could also be used in other product markets. This would improve legal certainty for undertakings by allowing them to assess what types of risks or costs would bring their agreements within the scope of competition rules.